Component modelling of low-damage beam-to-column joints equipped with friction dampers. (December 2022) - Latour, Massimo; Santos, Ana Francisca; Santiago, Aldina; Ferrante Cavallaro, Giovanni; Piluso, Vincenzo
Abstract: Friction joints have recently been shown to be an up-and-coming solution to limit the structural damage of steel moment-resisting frames under extreme seismic actions. Their main feature is the ability to concentrate the energy dissipation in a friction damper installed in the connection, protecting the remaining structural elements (beams, columns, joint components) from damage. Within a broader work devoted to assessing the response of friction joints, within this paper, new experimental results and an analytical model based on the component method of Eurocode 3 Part 1–8 are presented. The possibility of relying on a tool to predict the cyclic behaviour of partial-strength beam-to-column joints, such as those investigated in this paper, allows designers to account correctly for the non-linear response of joints in seismic time-history analyses. In addition, the availability of mechanical models to accurately predict the degradation of the slip properties of friction joints allows to avoid or strongly limit the number of tests required for the prequalification of partial-strength joints suggested by Eurocode 8. The proposed mechanical model is presented in this paper, showing its accuracy by comparison with cyclic tests of both internal and external joint configurations tested at the University of Coimbra and University of Salerno.